Analisis Pertanyaan Pada Buku Teks Kimia SMA ANALISIS PERTANYAAN PADA BUKU TEKS KIMIA SMA KELAS X BERDASARKAN KEMAMPUAN BERPIKIR KRITIS - Burhanudin Milama; Rahmah Nur Sabrina; Luki Yunita (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2022)
Chemistry textbooks' questions are important in improving students' thinking skills. Various types of questions are developed, but the effectiveness of these questions in supporting student success is something that is not expressed enough. This study aims to determine aspects of critical thinking skills developed in questions in the Chemistry High School textbook. The research method used is a descriptive method and multistage sampling technique. There are six books analyzed. The research instrument used was in the form of observation sheets classifying questions based on indicators of critical thinking skills. The results showed that the questions developed in Chemistry textbooks were analyzed based on critical thinking skills, including aspects of making simple explanations with a percentage of 28.8%, building basic skills of 20.3%, concluding at 45.8%, giving further explanations of 3.4%, and set strategy and tactics of 1.7%. The questions developed are dominated by concluding questions. Thus, it can be concluded that the questions in the Chemistry High School textbook have not been developed evenly on the five aspects of critical thinking.